Production of lytic enzymes by Trichoderma spp. and their effect on the growth of phytopathogenic fungi - Witkowska, D; Maj, A (Folia microbiologica, 2002)
The production of beta-1,3-glucanases and chitinases by three strains of Trichoderma in submerged cultures was determined. The synthesis of enzymes was induced by cell wall biopolymers of phytopathogenic fungi (Botrytis cinerea, Fusarium culmorum and F. oxysporum). T. hamatum produced the highest beta-1,3-glucanase activity; the most effective inducer of enzyme synthesis was the biomass of F. oxysporum. All examined strains of Trichoderma inhibited phytopathogen growth in biotic tests. The diffusion tests showed that the lytic enzymes take part in growth inhibition of phytopathogenic fungi.
Keywords: nemoci rostlin; beta-Glucosidase; Microbial Sensitivity Tests; Plant Diseases; substrátová specifita; Trichoderma; beta-glukosidasa; Substrate Specificity; Botrytis; Fusarium; Chitinases; chitinasy; glukan-1,3-beta-glukosidasa; Glucan 1,3-beta-Glucosidase; mikrobiální testy citlivosti